Physico-Chemical Properties of Palm-Based Diacylglycerol Oils in Blend with Palm-Based Oils - Saberi, Amir Hossein (2011)
Physico-chemical properties of palm-based diacylglycerol (P-DAG) oils as new functional fats were studied individually and in blends with palm-based oils (P-oil) to obtain basic information for development of functional palm-based DAG-enriched plastic fat products. P-DAG oils were produced through enzymatic glycerolysis of palm kernel oil (PKO), palm oil (PO), palm olein (POL), palm mid fraction (PMF) and palm stearin (PS) with the high DAG purity range of 83-90% (w/w). Reversed-phase high-performance liquid chromatography method using charged aerosol detector (CAD) was developed for separation of 1,3- and 1,2(2,3)-positional isomers of P-DAG oils including PKO-based DAG (PKO-DAG) as the sources of short- and medium-chain DAGs, and PO-based DAG (PO-DAG), PMF-based DAG (PMF-DAG), POL-based DAG (POL-DAG) and PS-based DAG (PS-DAG) as sources of long-chain DAG but with different ratios. In this method, linear gradient of acetone and acetonitrile was used and total retention time (RT) of 28 min was attained. Identification of P-DAG molecular species was accomplished using synthetic DAG standards. Physico-chemical properties of P-DAG oils were also evaluated and compared with their corresponding P-oils. P-DAG oils as compared to P-oils were found to have significantly (P<0.05) different FACs, Iodine values (IV) and slip melting points (SMP) and less steep solid fat content (SFC) profiles with higher complete melting temperatures. Also, P-DAG oils in contrast with P-oils showed endothermic as well as exothermic peaks at higher temperature regions, higher crystallization onset (TO) and higher heat of fusion (ΔHf) and crystallization. Crystal forms for P-DAG oils were mostly β. Crystallization kinetics of PO in the presence of different concentrations (2, 5, 10, 30 and, 50% w/w) of PO-DAG were investigated using Avrami model. Comparison of induction time (Ti), Avrami exponent (n), Avrami constant (k) and half-time of crystallization (t1/2) of blends showed that addition of 5% of PO-DAG in most of the supercooling ranges significantly (P<0.05) reduced nucleation rate as well as crystal growth velocity of PO. On the other hand, high concentrations of PO-DAG were found to significantly (P<0.05) reduce Ti as well as t1/2 and also increase k suggesting their promoting effects on nucleation and crystallization rate of PO. PO and PO blends with 2 and 5% of PO-DAG showed crystal transformation at crystallization temperatures (TCr) of 26, 26, 26.5°C, respectively as reflected in corresponding changes of the Avrami parameters at below and above these TCr. Presence of 10% PO-DAG showed β'-stabilizing effect on PO. Phase behaviour of binary blends containing PO and PO-DAG with 10% interval was also studied. The minor eutectic effects were observed at around 20-50% PO-DAG in SFC iso-lines of 20-50%. Phase behavior predicted by iso-solid diagram as well as isothermal SFC did not account for hardness variations observed between PO and PO blends with 10-40% PO-DAG. However, as concentration of PO-DAG increased from 40 to 100%, iso-lines temperatures, isothermal SFC and also hardness were found to steadily increase. On the other hand, hardness variations observed among PO and PO blends with 10-40% PO-DAG could be attributed to the respective DSC data as well as polymorphism changes. PO-DAG at 10% concentration was found to have β'-stabilizing effect on PO polymorphism while a β-form increasing trend was observed as concentration of PO-DAG increased from 10% to 90%. Ternary phase behaviour of sunflower oil (SFO), palm kernel olein (PKOL) and POL-DAG, and POL, PKO and PO-DAG were analyzed using isosolid diagrams of SFC and ΔSFC, and melting and solidification properties in two different ternary systems. The eutectic behaviour was observed along the binary line of PKOL/POL-DAG at temperature ranges of 5-20°C in the former system. However, no eutectic interaction was observed along the binary lines of SFO/PKOL as well as SFO/POL-DAG despite showing deviation from SFC (ΔSFC) within temperature range of 5-25°C. The most intensive eutectic interaction was observed along the binary line of PKO/PO-DAG followed by POL/PKO and POL/PO-DAG in the latter system. In general, it was found that ΔSFC does not always lead to eutectic behaviour and also the higher ΔSFC did not always lead to more intensive eutectic behaviour among the blends. Palm-based DAG-enriched soft tub margarine (PDAG-TM) containing SFO/PKOL/POL-DAG (35/15/50, (w/w)) was optimally formulated through analysis of multiple isosolid diagrams, and was found to have quite similar SFC profile as well as SMP but also lower saturated fatty acid (SAFA) as compared to the commercial soft tub margarine (CTM). Palm-based DAG-enriched shelf-stable margarine (PDAG-SSM) consisting of POL/PKO/PO-DAG (42.5/42.5/15, (w/w)) was also optimally formulated through analysis of multiple isosolid diagrams and was found to have quite similar SFC profile with commercial shelf-stable margarine (CSM).